Cinaciguat (BAY-582667) Modifies Cardiopulmonary and Systemic Circulation in Chronically Hypoxic and Pulmonary Hypertensive Neonatal Lambs in the Alto Andino - Beñaldo, Felipe A.; Araya-Quijada, Claudio; Ebensperger, Germán; Herrera, Emilio A.; Reyes, Roberto V.; Moraga, Fernando A.; Riquelme, Alexander; Gónzalez-Candia, Alejandro; Castillo-Galán, Sebastián; Valenzuela, Guillermo J.; Serón-Ferré, María; Llanos, Aníbal J. (Frontiers in Physiology, 2022)
Neonatal pulmonary hypertension (NPHT) is produced by sustained pulmonary vasoconstriction and increased vascular remodeling. Soluble guanylyl cyclase (sGC) participates in signaling pathways that induce vascular vasodilation and reduce vascular remodeling. However, when sGC is oxidized and/or loses its heme group, it does not respond to nitric oxide (NO), losing its vasodilating effects. sGC protein expression and function is reduced in hypertensive neonatal lambs. Currently, NPHT is treated with NO inhalation therapy; however, new treatments are needed for improved outcomes. We used Cinaciguat (BAY-582667), which activates oxidized and/or without heme group sGC in pulmonary hypertensive lambs studied at 3,600m. Our study included 6 Cinaciguat-treated (35 ug kg-1 day-1 x 7days) and 6 Control neonates. We measured acute and chronic basal cardiovascular variables in pulmonary and systemic circulation, cardiovascular variables during a superimposed episode of acute hypoxia, remodeling of pulmonary arteries and changes in the right ventricle weight, vasoactive functions in small pulmonary arteries, and expression of NO-sGC-cGMP signaling pathway proteins involved in vasodilation. We observed a decrease in pulmonary arterial pressure and vascular resistance during the acute treatment. In contrast, the pulmonary pressure did not change in the chronic study due to increased cardiac output, resulting in lower pulmonary vascular resistance in the last 2 days of chronic study. The latter may have had a role in decreasing right ventricular hypertrophy, although the direct effect of Cinaciguat on the heart should also be considered. During acute hypoxia, the pulmonary vascular resistance remained low compared to the Control lambs. We observed a higher lung artery density, accompanied by reduced smooth muscle and adventitia layers in the pulmonary arteries. Additionally, vasodilator function was increased, and vasoconstrictor function was decreased, with modifications in the expression of proteins linked to pulmonary vasodilation, consistent with low pulmonary vascular resistance. In summary, Cinaciguat, an activator of sGC, induces cardiopulmonary modifications in chronically hypoxic and pulmonary hypertensive newborn lambs. Therefore, Cinaciguat is a potential therapeutic tool for reducing pulmonary vascular remodeling and/or right ventricular hypertrophy in pulmonary arterial hypertension syndrome.